Harsh parenting and non-suicidal self-injury in adolescence: the mediating effect of depressive symptoms and the moderating effect of the COMT Val158Met polymorphism - Jinmeng Liu (BMC, 2021)
Abstract Background Previous studies have suggested that negative parenting environments, especially harsh parenting, are a specific risk factor for non-suicidal self-injury (NSSI). However, the potential mechanism between harsh parenting and NSSI has not been explored. Based on the experiential avoidance model and empirical research, we aimed to examine whether depressive symptoms are a mediator between harsh parenting and NSSI. Moreover, the catechol-O-methyltransferase (COMT) Val158Met polymorphism related to depressive symptoms may also exert a moderating effect on NSSI; thus, the interaction between harsh parenting and COMT was also considered in our study. Methods A total of 373 junior high school students were recruited for the study by using a longitudinal design. The adolescents answered self-report questionnaires and provided saliva samples for DNA genotyping. Results The results revealed that harsh parenting was positively associated with NSSI after 24 months, and this association was mediated by depressive symptoms. Moreover, the moderating role of COMT in the direct and indirect effects of harsh parenting on NSSI was observed only among adolescents with two Val alleles and the relationship was not significant for Met carriers. Conclusions Genetic variations of COMT Val158Met may be a critical candidate in understanding the development of depression and NSSI. We conclude that Val homozygotes of the COMT Val158Met polymorphism play a role in susceptibility to both depressive symptoms and NSSI.